SPECIFIC ASPECTS OF THE FORMATION OF YOUTH LEADERSHIP TRAINING IN NEW UZBEKISTAN - Makhmudov Komal Samadovich (American Journals, 2024)
This article reveals specific examples of important and necessary aspects of State Youth Policy in our country, the results of reforms in the field of Youth Policy, large-scale reforms in the formation of leadership in youth through state Youth Policy, their results, innovations in youth policy and the harmonious movement of society, state and youth, important aspects of youth leadership.
Keywords: New Uzbekistan, democracy, Citizen, Young Citizens, leader, Youth Leader, Leader, young leader, informal leader.